2018
DOI: 10.1371/journal.pone.0192004
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the outcomes of stent implantation in mini-swine model

Abstract: Sex-related differences have been noted in cardiovascular anatomy, pathophysiology, and treatment responses, yet we continued to drive evaluation of vascular device development in animal models without consideration of animal sex. We aimed to understand sex-related differences in the vascular responses to stent implantation by analyzing the pooled data of endovascular interventions in 164 Yucatan mini-swine (87 female, 77 male). Bare metal stents (BMS) or drug-eluting stents (DES) were implanted in 212 coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Contrary to expectations, ongoing device-related events are observed up to three years after poly-lactic acid-based BVS implantation 1,8 . BVS elastic recoil due to the lower radial strength of poly-lactic acid-based BVS 3,22 , and ongoing inflammation accompanying the resorption process which promotes thrombosis and neoatherosclerosis might explain these findings 7,23,24 . The TLR rates in our study were 7.5% among women and 12.4% among men, which differ from rates reported in selected stable populations of randomised trials, 3.7% vs 4.8%, respectively 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to expectations, ongoing device-related events are observed up to three years after poly-lactic acid-based BVS implantation 1,8 . BVS elastic recoil due to the lower radial strength of poly-lactic acid-based BVS 3,22 , and ongoing inflammation accompanying the resorption process which promotes thrombosis and neoatherosclerosis might explain these findings 7,23,24 . The TLR rates in our study were 7.5% among women and 12.4% among men, which differ from rates reported in selected stable populations of randomised trials, 3.7% vs 4.8%, respectively 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Since this tissue is most probably inflammation-triggered fibrin deposition, it leads to impaired neointimal BVS strut coverage, late malapposition and neoatherosclerosis formation. Although there are no data about sex-related differences in vascular response to BVS implantation, a large animal study demonstrated temporal sex-related differences in the extent and timing of resolution of inflammation and fibrin clearance after DES implantation 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Although clinically several sex-related differences in cardiovascular anatomy, pathophysiology and intervention response have been identified (60)(61)(62), sex is rarely evaluated in short-term pre-clinical animal models as a confounding variable. In 2018 Kunio et al (63) examined the sex-related differences in the outcome of endovascular stent implantation in swine. They found that female swine had histopathological signs of vascular injury and inflammation for longer than males and that adventitial fibrosis and neointimal fibrin deposition (thickening of arterial walls and decreased arterial lumen space) were greater in males than females.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experimentation is frequently employed to assess the efficacy and safety of new treatments before they are applied in clinical trials. [1][2][3][4][5][6][7][9][10][11][12][13][14][15]24 Although pigs have been used extensively in many areas, such as genomics, organ transplantation, oncology, trauma, and neurological and cardiovascular diseases, 2-4,10,18 many important physiological and anatomic factors remain unknown or have only been described superficially. 1,5,25 The literature contains several conflicting anatomic descriptions, such as the "bifurcation" of the aorta, 3,6,26 which is actually a "trifurcation" in pigs.…”
Section: Pig Models For Training and Experimentationmentioning
confidence: 99%
“…13 At 3 months of age, weighing from 32.4 to 34.5 kg, the same breed has been used to study microsurgical vascular anastomoses in a model of tibia transplantation 9 and, at 4 months of age, has been used to evaluate differences between the sexes with relationship to the results of coronary stenting. 24 The Göttingen minipig breed has been used in tomographic studies of vascular anatomy, more specifically with a focus on pediatric issues, since at 11 weeks of life, these animals have approximately the same weight as a newborn human being, 3 with an appropriate profile for these projects.…”
Section: Pig Models For Training and Experimentationmentioning
confidence: 99%